PENGARUH STRATEGI METAKOGNITIF TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM PENCERNAAN DI SMAN BANDA ACEH - Hasanuddin Hasanuddin; Khairil Khairil; Samingan Samingan; Ismul Huda; Agustina Agustina (Biotik, 2020)
This study aims to determine the effect of metacognitive strategiy on critical thinking skills and student learning outcomes in human digestive system material at SMAN 5 and SMAN 12 in Banda Aceh. This research was conducted in the second semester of the 2018/2019. The method used in this study is Experimental with the Pretest Posttest Control Group Design. The subjects of the study were all students of class XI IPA in both SMAN 5 and SMAN 12 Banda Aceh. The students of SMAN 5 from class IPA 4 was used as the control class meanwhile students from class IPA 2 as the experimental class. Students in SMAN 12 from class IPA 1 was used as control class meanwhile students from class IPA 2 as the experimental class. Data analysis was carried out by normality, homogeneity and t-test. The results showed that the use of metacognitive strategiy had an effect on students' critical thinking abilities, this can be seen from the results of the t-test in SMAN 5, namely t-hit 15,59 > t-tab 1,64 and in SMAN 12 namely t- hit 15,32 > t-tab 1,645, as well as influencing the cognitive learning outcomes of students, seen in the results of the t-test in SMAN 5 namely 10,07 > t-tab 1,64 and in SMAN 12 which is 3,68 > t-tab 1,64. The conclusion is that the use of metacognitive strategiy influences critical thinking skills and student learning outcomes in SMAN 5 and SMAN 12 in Banda Aceh.